COMPARATIVE STUDIES ON GROWTH AND EVALUATION OF SOME HARVESTED PARTS OF FLUTED PUMPKIN (TELFAIRIA OCCIDENTALIS HOOK F.) PLANTS - N. F 1Chukwurah.; S. C. 2Eze; C. B. 1Aruah; C. C. 2Onyeonagu; C. C.3Onyeke. (Journal of Animal and Plant Sciences, 2015)
A study was conducted to compare the growth and evaluation of some harvested parts of fluted pumpkin plants. Two field experiments in two planting seasons (2009 and 2010) were used for the study. A total of 500 plants in each planting season were studied at the Teaching and Research Farm of the Department of Crop Science, Faculty of Agriculture, University of Nigeria, Nsukka. The results showed that the male fluted pumpkin partitioned large number of their photosyntates in tendril production and subsequently slow growth and low fresh yield while, the female partitioned greater part of their photosyntates in leave production, faster growth and higher fresh yield.  The total number of tendrils harvested from males during the first (2009) and second (2010) planting seasons were 261.5 and 251.6 respectively while the total number of tendrils harvested from the females during the first and second planting seasons were 78.2 and 73.1 respectively.  On the contrary, number of leaves per plant was harvested from the male less than female plants, while 597.0 and 590.8 leaves per plant were harvested from the male plants during the first and second planting seasons, respectively while 712.9 and 742.3 leaves per plant were harvested from the female counterpart during the first and second planting seasons respectively. There was a significant difference (P < 0.05) between the male and female plants with respect to both number of leaves and tendrils per plant.  More vines were also harvested from the female gender than the males.
Keywords: Telfairiaoccidentalis; vegetative growth; yield evaluation; photosynthates